Lightning Occurrence between 2016 and 2020 in Fusagasugá, Cundinamarca, Colombia - Díaz-Ortiz, Fernando; Perilla López, Neyder; Ospina Carrillo, Juan Pablo; Cifuentes Guerrero, Pedro (Ingeniería, 2024)
Context: Lightning is a powerful natural phenomenon that poses a risk to life and infrastructure, given the enormous amounts of energy it can transfer in short periods of time, especially in cloud-to-ground strikes. Since lightning requires specific meteorological conditions for its generation, its occurrence is often influenced by conditions such as topography, rainfall, and wind patterns. Therefore, having information about lightning occurrences in a region is crucial for comprehensive risk management against this extreme natural phenomenon. Methods: In this study, we implemented a methodology based on knowledge discovery in databases (KDD) to analyze and visualize data provided by Vaisalas's GLD360 lightning location network. Results: The results indicate that, in Fusagasugá, Cundinamarca, there are two lightning activity peaks: one in the first half of the year (March) and another in the second half (October). Lightning events are most frequent during the afternoon, with a peak around 5:00 p.m. (local time). Additionally, most lightning events occur in two areas with low population density, covering 25% of the territory and ranging from 500 to 1000 meters above sea level. Conclusions: These findings highlight the importance of precise knowledge regarding the location of lightning events for planning prevention and risk management. In this case, efforts and resources should primarily focus on a small proportion of the municipality to substantially impact the population and infrastructure.